2015
DOI: 10.1007/s10509-015-2311-x
|View full text |Cite
|
Sign up to set email alerts
|

Statistical study of observed and intrinsic durations among BATSE and Swift/BAT GRBs

Abstract: Studies of BATSE bursts (Kouveliotou et al. 1993) have resulted in the widespread adoption of a two-group categorization: long bursts (those with durations ≥ 2 seconds) and short bursts (those with durations ≤ 2 seconds). This categorization, one must recall, used the observed T 90 time durations for bursts (during which 90% of a burst's fluence is measured).In this work, we have explored two ideas: 1) a statistical search for a possible third, intermediate category of bursts (between the "short" and the "long… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
88
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(94 citation statements)
references
References 39 publications
(61 reference statements)
5
88
1
Order By: Relevance
“…As the sum of two normal distributions is skewed, which is the apparent case in the Fermi sample, the underlying multimodal distribution may not necessarily be composed of Gaussians. Recently, Zitouni et al (2015) suggested that the duration distribution corresponding to the collapsar scenario (associated with long GRBs) might not necessarily be symmetrical because of a non-symmetrical distribution of envelope masses of the progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…As the sum of two normal distributions is skewed, which is the apparent case in the Fermi sample, the underlying multimodal distribution may not necessarily be composed of Gaussians. Recently, Zitouni et al (2015) suggested that the duration distribution corresponding to the collapsar scenario (associated with long GRBs) might not necessarily be symmetrical because of a non-symmetrical distribution of envelope masses of the progenitors.…”
Section: Discussionmentioning
confidence: 99%
“…AIC and BIC have also been previously used for GRB classification by a number of authors (Mukherjee et al 1998;Tarnopolski 2016a,b;Yang et al 2016;Zhang et al 2016b). Frequentist model comparison after binning the data has been used by Zitouni et al (2015); Tarnopolski (2015). More information about AIC and BIC and its application to a variety of astrophysical problems can be found in Liddle (2004Liddle ( , 2007; Tan & Biswas (2012); Shi et al (2012);Shafer (2015).…”
Section: Model Comparisonmentioning
confidence: 99%
“…Zhang & Choi (2008) analysed the duration distribution of 95 redshift-known Swift GRBs and found that the intrinsic duration is still bimodal. Zitouni et al (2015) found that 3 groups were statistically better that 2 groups after studying the intrinsic duration distribution of a larger datasets redshift-known Swift GRBs, which contains 248 GRBs. Tarnopolski (2016a) analysed the distribution of 947 Swift GRBs' observed duration and 347 redshift-known GRBs' duration in both observer and rest frames.…”
Section: Introductionmentioning
confidence: 96%